A Strain‐Regulated, Refillable Elastic Patch for Controlled Release. Issue 9 (8th February 2016) - Kim, Bongsoo; Yoo, SangHyuk; Kim, Yong‐Jin; Park, Jaeyoon; Kang, Byunghoon; Haam, Seungjoo; Kang, Sun‐Woong; Kang, Keonwook; Jeong, Unyong
Abstract : Many stimulus‐induced release systems have been studied for the smart control of drug delivery. Mechanical strain is rarely investigated as means of stimulation for these systems, despite the fact that there are many biological processes and human body motions that involve strain changes. In this study, a design for a stretchable reservoir‐based patch‐type release system is suggested. The reservoir made of an elastomer undergoes a decrease in volume when the system is deformed by bending and stretching. The response is predicted by finite element method modeling studies. The release rate of the reservoir is finely controlled by attaching elastic microchannels with different channel lengths. Because the whole system is made of rubber, the patch is deformable and the solution can be refilled with a microsyringe. Systematic designs for on/off release, long‐term release, and short‐term release are suggested. Abstract : A refillable, elastic drug release patch that is responsive to external strain is suggested. The response is predicted by finite element method modeling. The release behavior is finely controlled by the attached microchannel. Systematic designs for on/off release and various controlled releases are realized.